Valorizing the usage of olive leaves, bioactive compounds, biological activities, and food applications: A comprehensive review - Selim, Samy; Albqmi, Mha; Al-Sanea, Mohammad M.; Alnusaire, Taghreed S.; Almuhayawi, Mohammed S.; AbdElgawad, Hamada; Al Jaouni, Soad K.; Elkelish, Amr; Hussein, Shaimaa; Warrad, Mona; El-Saadony, Mohamed T. (Frontiers in Nutrition, 2022)
Olive oil production is a significant source of economic profit for Mediterranean nations, accounting for around 98 percent of global output. Olive oil usage has increased dramatically in recent years, owing to its organoleptic characteristics and rising knowledge of its health advantages. The culture of olive trees and the manufacture of industrial and table olive oil produces enormous volumes of solid waste and dark liquid effluents, involving olive leaves, pomace, and olive oil mill wastewaters. These by-products offer an economic issue for manufacturers and pose major environmental concerns. As a result, partial reuse, like other agronomical production wastes, is a goal to be achieved. Because these by-products are high in bioactive chemicals, which, if isolated, might denote components with significant added value for the food, cosmetic, and nutraceutical sectors, indeed, they include significant amounts of beneficial organic acids, carbohydrates, proteins, fibers, and phenolic materials, which are distributed differently between the various wastes depending on the olive oil production method and table olive agronomical techniques. However, the extraction and recovery of bioactive materials from chosen by-products is a significant problem of their reasonable value, and rigorous detection and quantification are required. The primary aims of this review in this context are to outline the vital bioactive chemicals in olive by-products, evaluate the main developments in extraction, purification, and identification, and study their uses in food packaging systems and safety problems.